(untitled) (Biological Sciences - PJSIR, 2019)
Three experiments were conducted to check Coptotermes heimi termites mortality in different conditions. In first experiment, two termiticides; fipronil and imidacloprid of specific formulation 25 EC and 5% SC, respectively, were used. Different concentration dilutions were prepared and termites? mortality assay was performed. Both formulations gave 100% termites mortality on their highest ppm concentration after one week. Second experiment was based on different spore concentrations of Metarhizium anisopliae that were applied on worker termites to check the lethal concentration of fungi. It was observed that spore concentration showed direct relationship with termites? mortality which means, as the spore concentration increases, termite mortality also increases. Last experiment was conducted to check the synergistic effect of M. anisopliae and termiticides. The fungus was used in combination with termiticides, fipronil and imidacloprid, separately. The rate of mortality of termites which exposed to imidacloprid/fipronil and M. anisopliae simultaneously was higher than mortality of termites exposed to either treatment alone.